Tobacco Use Among Transgender and Gender Non-conforming Adults in the United States. (May 2019) - Wheldon, Christopher W; Wiseman, Kara P
Background: Findings from previous population-based studies are in conflict regarding the relative use of tobacco products among transgender populations compared with their cisgender counterparts. The purpose of this study was to estimate the prevalence of current tobacco use among transgender persons in the United States and evaluate differences in relative use between transgender and cisgender respondents. Methods: This was a secondary analysis of data from the Population Assessment of Tobacco and Health (PATH) Study Wave 2 (October 2014 and October 2015). Differences in current use of cigarettes, e-cigarettes, and cigars were examined between self-identified transgender (n = 151) and cisgender (n = 27 557) respondents. Results: In multivariable analyses, transgender identity was not associated with any of the 3 tobacco behaviors or the summary measure of tobacco use (ie, any current use of cigarettes, e-cigarettes, or cigars). In each of the models, female binary sex (compared with male), older age, Hispanic ethnicity (compared with non-Hispanic white), higher household income, and higher educational attainment were independently associated with lower odds of current use of cigarettes, e-cigarettes, or cigars, whereas sexual minority identity (ie, gay/lesbian or bisexual) was independently associated with higher odds of use. Conclusions: The prevalence of the use of cigarettes, e-cigarettes, and cigar use was statistically equivalent between transgender and cisgender populations in this national study of adults in the United States, which differs from previous research showing higher rates of tobacco use among transgender individuals. Differences in tobacco use that were identified were fully explained by sociodemographic characteristics (eg, income and education) between the transgender and cisgender populations.